Pro-Kontra dalam Mengamalkan Hadis Ahad Sebagai Otoritas Agama Islam - Syahidin Syahidin; Agusri Fauzan; Ilham Syukri (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2020)
Based on the quantity of narrators, hadith is divided into two, namely mutawatir and Ahad. Most of the teachings of Islam, be it creed or other problems, rely on the hadith ahad. If the ahad hadith cannot be used as evidence, then the consequence is that many Islamic teachings that are understood and believed by the majority of Muslims so far will be displaced. The discourse categorization of hadiths into mutawatir and Ahad will have an impact on the emergence of doubts and even rejection of the authority of the hadiths as a source of Islamic teachings after the Qur'an, which also means doubting most of the traditions of the Prophet Muhammad. This study aims to see the pros and cons. in practicing the hadith ahad. The method used in this research is a qualitative method through the documentation of data collection techniques, this technique is carried out by examining documents related to the authenticity of the ahad hadith in some hadith literature and other works. The data analysis is descriptive analysis and comparative. The results of the research show that even though these ahad hadiths do not show conviction, he shows them to strong suspicion, and they have become the legal basis before the mutawatir-ahad dichotomy appeared. In fact, the opinion that states that these ahad traditions cannot be used as evidence, even in matters of faith, is the opinion of bid'ah, has no basis in Islamic syari'at. The status of ahad hadith authenticity is consensus accepted through the arguments that have been explained by the scholars to refute some of the scholars who reject it.